Van Der Waals driven self-assembly approch for ZnS nanoparticles - Noor Azie Azura, Binti Mohd Arif; Chong, Chee Jiun (UMT Publisher, 2018)
Thin film nanoparticles have been prepared on glass substrate by spin coating and self assembly method. Combination techniques were used to study on structural thin film using Field Emission Scanning Electron Microscopy (FE-SEM) and the elements were confirmed using Energy Dispersive X-Ray (EDX). The results of this experiment showed that the well-organized nanoparticles were produced with the size of nanoparticle 30-50 nm. EDX analysis confirmed the ZnS nanoparticles with percentage of Zn = 24.9% and S = 0.6 %. Using Van der Walls equation, formation of larger size of nanoparticles influence strong result in van der Waals relation between particles. This outcome can be used to develop nanomaterials in the future.